Physico-chemical properties and fatty acid composition of Chrozophora tinctoria seeds as a new oil source - S. Hazrati; S. Nicola; S. Khurizadeh; A. Alirezalu; H. Mohammadi (Grasas y Aceites, 2019)
Chrozophora tinctoria L., usually known as dyer’s Croton, Turnsole or Giradol, has been used in various medicinal and food products for many years. However, no comprehensive research has been undertaken to assess its potential as a new seed oil crop. Therefore, the current study examined the fatty acid composition, physico-chemical properties and antioxidant activity of C. tinctoria seeds, grown in the southwest of Iran. The seed oil content was found to be 26.40%. The extracted oil was analyzed for fatty acid composition using gas chromatography (GC). The results showed that unsaturated fatty acids accounted for almost 91% of the total fatty acids. Linoleic acid was the dominant fatty acid (76.68%), followed by oleic acid (13.99%) and palmitic acid (5.32%). δ-tocopherol was the major tocopherol in the oil, representing 70 mg/100 g oil. The total phenolic content (151.70 mg GAE per 100 g oil) and total flavonoid content (1.17 mg QE oil) were also determined in the extracted oil. The antioxidant activity was measured by a DPPH assay and expressed as 45% of the seed oil. Due to its high oil yield and high unsaturated fatty acid content, C. tinctoria could be regarded as a new source of edible oil.